2013
DOI: 10.1002/nau.22496
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the urogenital distress inventory (UDI-6) and incontinence impact questionnaire (IIQ-7) in a Dutch population

Abstract: The Dutch UDI-6 and IIQ-7 are reliable, valid, and responsive instruments for assessing symptom distress of urinary incontinence and its impact on daily life in both men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 36 publications
3
69
1
2
Order By: Relevance
“…A higher score indicates more impact on daily life of UI. The IIQ-7 has shown to be a reliable, valid, and responsive instrument for assessing the impact on daily life of UI; this also applies for the Dutch version [24] .…”
Section: Secondary Outcomes Subjective Outcome Measurementsmentioning
confidence: 91%
See 1 more Smart Citation
“…A higher score indicates more impact on daily life of UI. The IIQ-7 has shown to be a reliable, valid, and responsive instrument for assessing the impact on daily life of UI; this also applies for the Dutch version [24] .…”
Section: Secondary Outcomes Subjective Outcome Measurementsmentioning
confidence: 91%
“…Again, a short version has been developed [23] . The UDI-6 is divided into 3 domains (irritative, stress and obstructive) and has shown to be a reliable, valid and responsive instrument for assessing symptom distress of urinary incontinence, also in the Dutch population [24] .…”
Section: Secondary Outcomes Subjective Outcome Measurementsmentioning
confidence: 99%
“…The Urinary Distress Inventory and Incontinence Impact Questionnaire assess symptom distress and the impact on daily life of urinary incontinence. 11 The visual analog scale measured the subjective distress of the patients (scale 0-10). All surgical options, including bulking agents, adjustable balloons, and male sling have been offered to the patients.…”
Section: Methodsmentioning
confidence: 99%
“…Noteworthy, the IIQ-7 also captured small positive changes in female patients with a stable GRS health condition and in male patients with a worsened GRS health condition (although the difference in males was not statistically significant). A validation study in a Dutch population also showed similar findings of small positive changes of the IIQ-7 in patients with stable or worsened health status (Utomo et al 2013). The improvement in patients with worsened health status might be related to the trajectory of health outcomes in LUTS (Revicki et al 2006).…”
Section: Hrqol Measuresmentioning
confidence: 60%